MOTIVASI BELAJAR PADA PESERTA DIDIK KELAS X SMKN 1 PONTIANAK TAHUN AJARAN 2017/2018 - Labret, Anassia; Wicaksono, Luhur; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractMotivation to learn is a series of business or impulse that causes someone to want and want to do something in achieving the desired objectives.The learning process that involves various components should be packaged in a systematic study. So that produce optimal learning results. The success of the learning process where the parameter is the result of learning, it is spurring both teachers and students to strive to achieve that goal. Therefore, researchers wanted to know the motivation to learn on Students of Class X SMK Negeri 1 Pontianak in Academic Year 2017/2018. A common problem in this research is